The Role of the School Principal in the Sahabat Bencana Program at SDN Tambakrejo 03 - Setianingsih, Wisnu Yuli; Soedjono, (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the role of the school principal in the implementation of the Sahabat Bencana program at SDN Tambakrejo 03, an elementary school in a coastal area vulnerable to flood disasters. Employing a qualitative approach with a case study design, data were collected through interviews, observations, and document analysis. The research informants included the school principal, teachers, staff, and local community members. The results indicate that the school principal plays a key role in leading the development of disaster preparedness plans, conducting training, and coordinating with external parties such as the Regional Disaster Management Agency (BPBD) and local government. The principal also ensures that all school members are actively involved in the program. However, the study identifies challenges related to limited resources, staff knowledge of emergency procedures, and suboptimal coordination with external parties. Despite these challenges, the Sahabat Bencana program has had positive impacts, such as increased awareness and preparedness among students, teachers, and staff. The program has also strengthened cooperation between the school and the community in disaster preparedness. This study contributes to disaster education management in coastal schools by providing insights into the key role of school leadership and the importance of collaboration with external agencies. The study recommends improvements in school infrastructure, more intensive training for staff, and better coordination with external parties to enhance the effectiveness of the program in the future.